Capture of Uropathogenic E. coli by Using Synthetic Glycan Ligands Specific for the Pap‐Pilus. Issue 2 (10th January 2013) - Yosief, Hailemichael O.; Weiss, Alison A.; Iyer, Suri S.
Abstract Biotinylated mono‐ and biantennary di‐/trisaccharides were synthesized to evaluate their ability to capture E. coli strains that express pilus types with different receptor specificities. The synthesized biotinylated di‐/trisaccharides contain Galα(1→4)Gal, Galα(1→4)GalNHAc, GalNHAcα(1→4)Gal, Galα(1→4)Galβ(1→4)Glc and GalNHAcα(1→4)Galβ(1→4)Glc as carbohydrate epitopes. These biotinylated oligosaccharides were immobilized on streptavidin‐coated magnetic beads, and incubated with different strains of live E. coli. Capturing ability was assessed by using a luciferase assay that detects bacterial ATP. The trisaccharides containing Galα(1→4)Galβ(1→4)Glc and the disaccharides containing Galα(1→4)Gal as the epitopes exhibited strong capturing ability for uropathogenic E. coli strains with the pap pilus genotype, including CFT073, J96 and J96 pilE. The same ligands failed to capture E. coli strains with fim, prs, or foc genotypes. Uropathogenic CFT073 was also captured moderately by biantennary disaccharides containing a GalNHAc moiety at the reducing end; however, other saccharides containing GalNHAc at the nonreducing end did not capture the CFT073 strain. These synthetic glycoconjugates could potentially be adapted as rapid diagnostic agents to differentiate between different E. coli pathovars.